THE EFFECTIVENESS OF COOPERATIVE LEARNING MODEL OF STAD THYPE BASED ON GAGNE LEARNING THEORY IN MATHEMATICS LEARNING CLASS VII AT MTS WITH B ACCREDITATION IN MAKASSAR CITY - Umar Umar (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2018)
The research aimed to discover the effectiveness of the implementations of cooperative learning model of STAD type based on Gagne learning theory in Mathematics learning of class VII at MTs with B Accreditation in Makassar City. The research was pre-experimental research. The population of the research were all of the srudents of class VII oatf MTs with B Accreditation in Makassar City. The samples were all of the students class VIIa at MTs AL-Fakhriyah Makassar and all of the students of class VIIa MTs AL-Hidayah Makassar. The data were collected by using instruments, namely learning implementation observation sheet, students’ activities observation sheet, student’ Mathematics interest questionnaire. The data were analyzed by using descriptive and inferential analysis. The result of the research showed that the learning implementation of the students in learning were in implemented very well category, the students’ activities in learning were in very active category, the student’ Mathematics learning result were in high category with the mean 82,19 and deviation standard 8,49, the proportion level of classical completeness was 0,95, the average of normalized gain of learning result was in high category, students’ responses on the impelementation of cooperative learning model of STAD type based on Gagne learning theory were in positive category with the average score 3,58. The students’ interest on the implementation of cooperative learning model of STAD type based on Gagne learning theory were in very high category with average 3,58. In general, it could be concluded that cooperative learning model of STAD type based on Gagne learning theory in Mathematics learning was effective to be implemented to the students of class VII at MTs with B Accreditation in Makassar City